Pulmonary Manifestations of Primary Immunodeficiencies in Children - A Review - Kabir, ARM Luthful; Roy, Sudipta (Bangladesh Journal of Child Health, 2018)
Primary immunodeficiency diseases (PIDs) are inherited defects of the innate or adaptive arms of the immune system that differs from secondary immunodeficiencies. Respiratory disorders are significant causes of morbidity and the leading causes of death (30% -65%) in both children and adults with PIDs. The spectrum of respiratory manifestations is extremely wide due to PIDs. PIDs are broadly classified according to the components of the immune system that is primarily disrupted. Predominant antibody deficiency disorders are the most frequent and comprise approximately 70-75% of all PIDs. The most common clinical manifestations are infections involving the respiratory tract e.g. rhinosinusitis, otitis media, bronchitis, bronchiectasis and recurrent pneumonia (30% -65%). Recurrent respiratory infections are often the first warning sign. Timely diagnosis and appropriate therapy can improve or at least decelerate the progression of these complications. Infectious and non-infectious respiratory complications determinate the patient’s prognosis. These complications are associated with significant morbidity and mortality in PID patients. Appropriate awareness of these manifestations is essential, especially for the pulmonologist to reduce morbidity and mortality in PID patients. Bangladesh J Child Health 2018; VOL 42 (2) :86-93